Maternal physiological calming responses to infant suckling at the breast - Nami Ohmura; Lana Okuma; Anna Truzzi; Gianluca Esposito; Kumi O. Kuroda (Journal of Physiological Sciences)
Abstract The mother–infant relation is key to infant physical, cognitive and social development. Mutual regulation and cooperation are required to maintain the dyadic system, but the biological foundation of these responses remains to be clarified. In this study, we report the maternal calming responses to infant suckling during breastfeeding. Using behavioral measures and a Holter electrocardiogram as a readout of the maternal autonomic nervous system, the maternal activities during resting, sitting with her infant on her lap, and breastfeeding were assessed. We found that during breastfeeding, mothers talked less and maternal heart rate was lower than during sitting with the infant without breastfeeding. Congruently, maternal heart rate variability measurements indicated a higher parasympathetic activity during breastfeeding. Time-locked analyses suggested that this maternal calming response was initiated by the tactile stimulation at the breast by the infant face or mouth latch, which preceded the perceived milk ejection. These findings suggest that somatosensory stimuli of breastfeeding activate parasympathetic activity in mothers. Just as how the infant Transport Response facilitates the carrying of infants, the maternal calming responses during breastfeeding may promote efficient milk intake by inhibiting spontaneous maternal activities.